6,7-Difluoro-1,2,3,4-tetrahydroquinoxaline-5,8-dicarbonitrile - Qu, Bao-Hua (International Union of Crystallography, 2013)
In the title compound, C(10)H(6)F(2)N(4), the C(ar)—N bonds are slightly shortened with respect to a standard aniline C—N bond [1.3580 (16) and 1.3618 (16) versus 1.39 Å], thus indicating some π–π conjgation with the electron-acceptor CN groups. The molecule, except for two C atom of the ethylene bridge, is nearly planar, the largest deviation of the other non-H atoms from the mean plane being 0.309 (2) Å. The N—C—C—N torsion angle involving the ethylene bridge is 50.23 (18)°. In the crystal, molecules are connected by pairs of N—H⋯N hydrogen bonds into chains along [21-1].